A Fokker–Planck code for laser plasma interaction in femtosecond-laser shock peening. (27th January 2016) - Ren, Zhencheng; Wang, Guo-Xiang; Ye, Chang; Dong, Yalin
Abstract: A Fokker–Planck code is developed to simulate the laser–plasma interaction in the femtosecond-laser shock peening and forming processes. A numerical scheme dealing with high-energy concentration and its resulting steep gradient are presented, and the source code is provided as supplementary material for further usage. The breakdown of the classical heat transport theory is observed when the laser intensity increases. The difference in heat flow between the classical theory and simulation is presented. It is found that the classical heat transport theory overestimates heat flow by orders of magnitude during femtosecond-laser shock peening or forming. As a result, the electron pressure can be underestimated using the classical hydrodynamic code.